2017
DOI: 10.3122/jabfm.2017.04.170112
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Opioid Use among Adults with Mental Health Disorders in the United States

Abstract: Background:The extent to which adults with mental health disorders in the United States receive opioids has not been adequately reported.Methods: We performed a cross-sectional study of a nationally representative sample of the noninstitutionalized U.S. adult population from the Medical Expenditure Panel Survey. We examined the relationship between mental health (mood and anxiety) disorders and prescription opioid use (defined as receiving at least 2 prescriptions in a calendar year).Results: We estimate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
144
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(161 citation statements)
references
References 26 publications
15
144
1
1
Order By: Relevance
“…Among Medicare enrollees aged 65 and older, the 10% who have disability as an original entitlement comprised 25% of prolonged opioid users and 40% of high‐dose users in 2015. One explanation for the high rate of risky opioid use among disability‐entitled enrollees is the clustering of known risk factors—mood disorders, cognitive disability, and back pain‐related disorders—associated with opioid misuse …”
Section: Discussionmentioning
confidence: 99%
“…Among Medicare enrollees aged 65 and older, the 10% who have disability as an original entitlement comprised 25% of prolonged opioid users and 40% of high‐dose users in 2015. One explanation for the high rate of risky opioid use among disability‐entitled enrollees is the clustering of known risk factors—mood disorders, cognitive disability, and back pain‐related disorders—associated with opioid misuse …”
Section: Discussionmentioning
confidence: 99%
“…The psychosocial context in which substance use exists has been linked to mental illness among criminal justice-involved African Americans (Calcaterra et al, 2014; Western et al, 2015). More specific to NMOU, cross-sectional studies (Davis et al, 2017), meta-analyses (Fischer et al, 2012), secondary analyses of population-based surveys (Ashrafioun et al, 2017), and longitudinal analysis (Martins et al, 2012) have revealed individuals who engage in NMOU are significantly more likely to have mental health problems. Others have posited NMOU is motivated by the desire to attenuate psychological distress (Martins et al, 2009; Martins et al, 2012).…”
Section: 0 Introductionmentioning
confidence: 99%
“…To examine whether there were differences in the depression and high-potency opioid use association as a function of arthritis diagnosis, we constructed additional multivariable logistic regression models controlling for gender, age, race/ethnicity, education, marital status, smoking status, BMI, diabetes, arthritis, hypertension, and cancer ( [12][13][14] This emerging body of literature should be of concern to professionals in geriatric psychiatry, gerontology, and other agingrelated disciplines, because it suggests that high-potency opioid medication is potentially interfering with safer, more appropriate mental health and medical treatment among high-risk older adults with severe depressive symptoms. 16 We deliberately examined whether there were differences in degree of association between high-potency opioid medication use and depression category as a function of arthritis diagnosis.…”
Section: Post Hoc Testsmentioning
confidence: 99%